2021
DOI: 10.1007/s00117-021-00891-7
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound perfusion imaging of organs

Abstract: In multimodal radiologic imaging, contrast-enhanced ultrasound (CEUS) is increasingly used. One of the advantages of CEUS is the possibility of repeated application of contrast media without decreasing renal function or affecting the thyroid gland. Small solid liver lesions can be diagnosed and detected with high accuracy. Moreover, solid lesions in other abdominal organs can also be characterized. Frequent applications for solid lesions in the near field concern thyroid tumors and lymph nodes. For prostate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
0
13
1
3
Order By: Relevance
“…Using US contrast media in the multiparametric assessment of malignant superficial LNs makes it possible to generate quantitative data, which could be used for therapy monitoring [ 18 , 19 , 22 , 23 ]. However, this procedure is, at present, not yet standard in routine clinical work, as the measurement parameters still vary widely [ 1 , 25 , 38 ]. Ye and colleagues have already shown that the peak intensity and time-to-peak in the early phase (after the 5th irradiation dose) of radiation therapy predict a treatment response of LN metastases from nasopharyngeal cancer with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using US contrast media in the multiparametric assessment of malignant superficial LNs makes it possible to generate quantitative data, which could be used for therapy monitoring [ 18 , 19 , 22 , 23 ]. However, this procedure is, at present, not yet standard in routine clinical work, as the measurement parameters still vary widely [ 1 , 25 , 38 ]. Ye and colleagues have already shown that the peak intensity and time-to-peak in the early phase (after the 5th irradiation dose) of radiation therapy predict a treatment response of LN metastases from nasopharyngeal cancer with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore the combination of conventional US and CEUS had the highest diagnostic accuracy (92.7%) compared with conventional US (80.8%) and CEUS (89.1%) alone in the diagnosis of LN metastasis from papillary thyroid carcinoma [ 23 ]. CEUS is already an established method in the therapy monitoring of liver tumors, as well as for other relevant indications, and offers an additional pathophysiological insight during and after a therapy sequence through the possibility of a high-resolution investigation of the perfusion kinetics, whereby the time–intensity curve (TIC) perfusion analysis represents a quantitatively measurable variable [ 24 , 25 , 26 , 27 ]. Time–intensity curve perfusion analysis has so far only been investigated a little in the assessment of cervical LN metastases and CEUS, for the characterization of superficial lymphadenopathy, at present, has not been recommended in guidelines for routine clinical use [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of CEUS in the present study compared with the findings of previously performed color Doppler sonography and contrast-enhanced CT studies are summarized in Table 4. The reason for the higher sensitivity of CEUS compared to a contrast-enhanced CT may be the strictly intravascular characteristics of the contrast medium of CEUS [22]; therefore, the non-perfused areas show an absence of enhancement during the complete CEUS examination, distinguished from perfused tissue. However, omental hernias were included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the higher sensitivity of CEUS compared to a contrast-enhanced CT may be the strictly intravascular characteristics of the contrast medium of CEUS [ 22 ]; therefore, the non-perfused areas show an absence of enhancement during the complete CEUS examination, distinguished from perfused tissue. However, omental hernias were included in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important limitations of CEUS in PCa diagnostics is the benign prostate metaplasia (BPH), which may obscure the tumor blood flow by increasing the size and vascularization of the transition zone. Furthermore, it might be difficult to detect PCa in the apical and dorsal prostate areas for which endoluminal and 3D CEUS multifrequency probes may be necessary [72]. Lastly, the bolus injection of the microbubble contrast agent provides only temporary enhancement during the intravascular phase, reducing the time to distinguish between PCa and surrounding benign tissue to less than one minute.…”
Section: Contrast-enhanced Ultrasoundmentioning
confidence: 99%